Pemetaan Praktek Dokter Umum dan Bidan di Kota Selong Berbasis GIS (Geographic Information System) - Amri Muliawan Nur; Aris Sudianto; Hariman Bahtiar; Muhammad Fauzi Zulkarnaen (Infotek: Jurnal Informatika dan Teknologi, 2023)
Selong City is one of the areas of the East Lombok district which has many health facilities. Apart from the hospital, one of the existing health facilities is the practice of general practitioners and midwives. The problem with this research is that there is very little information on the location of general practitioners and midwife practices in Selong City, for this reason, an appropriate system is needed to determine the location of general practitioners and midwife practices. This study aims to map the locations of GIS-based practice of general practitioners and midwives to facilitate the community's need in knowing the locations of general practitioners and midwife practice quickly and precisely. The application is made web-based using the Google Maps API. The application that has been made can provide a solution in conveying information quickly, precisely, and accurately, regarding the whereabouts of general practitioners' and midwives' practice locations in the city of Selong. This is because the public can access online the whereabouts of General Practitioners and Midwives' practices anytime and anywhere